Активізація діяльності міжнародних суфійських організацій - Брильов, Д. (Відділення релігієзнавства Інституту філософії ім. Г.С. Сковороди НАН України, 2010)
Статья Д.Брылёва «Активизация деятельности международных суфийских организаций» посвящена феномену международных суфийских организаций, возникших в ХХ столетии. Рассматривается влияние процессов глобализации на формирование современных суфийских движений и их противостояние с представителями радикальной идеологии в мусульманской умме. Ключевые слова: суфизм, Аль-Ахбаш, хабашити, исламизм, глобализация. The article of D.Briljov “The growing of activity of international Sufi organizations” is dedicated to analysis of evolution and activities of international Sufi organizations, which were formed in XX-th century. The author analyses the influence of the globalization processes on the foundation of contemporary Sufi movements and their conflict with the radical ideology in the Islamic society. Key words: Sufi, Al-Ahbash, Habashi, Islamism, globalization.